Kinin B1 and B2 Receptors Contribute to Cisplatin-Induced Painful Peripheral Neuropathy in Male Mice - Gabriela Becker; Maria Fernanda Pessano Fialho; Indiara Brusco; Sara Marchesan Oliveira (MDPI AG, 2023)
Cisplatin is the preferential chemotherapeutic drug for highly prevalent solid tumours. However, its clinical efficacy is frequently limited due to neurotoxic effects such as peripheral neuropathy. Chemotherapy-induced peripheral neuropathy is a dose-dependent adverse condition that negatively impacts quality of life, and it may determine dosage limitations or even cancer treatment cessation. Thus, it is urgently necessary to identify pathophysiological mechanisms underlying these painful symptoms. As kinins and their B1 and B2 receptors contribute to the development of chronic painful conditions, including those induced by chemotherapy, the contribution of these receptors to cisplatin-induced peripheral neuropathy was evaluated via pharmacological antagonism and genetic manipulation in male Swiss mice. Cisplatin causes painful symptoms and impaired working and spatial memory. Kinin B1 (DALBK) and B2 (Icatibant) receptor antagonists attenuated some painful parameters. Local administration of kinin B1 and B2 receptor agonists (in sub-nociceptive doses) intensified the cisplatin-induced mechanical nociception attenuated by DALBK and Icatibant, respectively. In addition, antisense oligonucleotides to kinin B1 and B2 receptors reduced cisplatin-induced mechanical allodynia. Thus, kinin B1 and B2 receptors appear to be potential targets for the treatment of cisplatin-induced painful symptoms and may improve patients' adherence to treatment and their quality of life.